Cetuximab and biomarkers in non-small-cell lung carcinoma - Patil, Nitin; Abba, Mohammed L.; Allgayer, Heike (Biologics, 2012)
Cancer progression is a highly complex process that is driven by a constellation of deregulated signaling pathways and key molecular events. In non-small-cell lung cancer (NSCLC), as in several other cancer types, the epidermal growth factor receptor (EGFR) and its downstream signaling components represent a key axis that has been found not only to trigger cancer progression but also to support advanced disease leading to metastasis. Two major therapeutic approaches comprising monoclonal antibodies and small molecule tyrosine kinase inhibitors have so far been used to target this pathway, with a combination of positive, negative, and inconsequential results, as judged by patient survival indices. Since these drugs are expensive and not all patients derive benefits from taking them, it has become both pertinent and paramount to identify biomarkers that can predict not only beneficial response but also resistance. This review focuses on the chimeric monoclonal antibody, cetuximab, its application in the treatment of NSCLC, and the biomarkers that may guide its use in the clinical setting. A special emphasis is placed on the EGFR, including its structural and mechanistic attributes.